Misdiagnosis analysis of 2291 cases of haematolymphoid neoplasms - Deng, Jing; Zuo, Xiaona; Yang, Liuyi; Gao, Zifen; Zhou, Chunju; Guo, Ligai (Frontiers in Oncology, 2023)
Objective To retrospectively analyze the reasons for misdiagnosis of haematolymphoid neoplasms and provide experience for improving the diagnostic level in China. Methods A retrospective analysis was performed on 2291 intractable cases of haematolymphoid diseases evaluated by the Department of Pathology of our hospital from July 1st, 2019, to June 30th, 2021. All 2291 cases were reviewed and classified by two hematopathologist experts according to the 2017 revised WHO classification criteria, supplemented immunohistochemistry (IHC), molecular biology and genetic information as needed. The diagnostic inconsistency between primary and expert review was evaluated. The possible causes of the diagnostic errors were analyzed for each step involved in the procedure of diagnosis. Results In total, 912 cases did not conform to the expert diagnoses among all the 2291 cases, with a total misdiagnosis rate of 39.81%. Among them, misdiagnosis between benign and malignant lesions accounted for 24.34% (222/912), misdiagnosis between haematolymphoid neoplasms and non-haematolymphoid neoplasms accounted for 3.29% (30/912), misdiagnosis among lineages accounted for 9.32% (85/912), misclassification in lymphoma subtypes accounted for 60.75% (554/912), and other misdiagnoses among benign lesions accounted for 2.30% (21/912) of cases, among which misclassification of lymphoma subtypes was the most common. Conclusion The accurate diagnosis of haematolymphoid neoplasms is challenging; however, it is important for precise treatment. Through this analysis, we aimed to highlight the importance of accurate diagnosis and to improve the diagnostic level in our country by strengthening systematic training for hematopathologists. Thereby, patients can receive treatment that is customized and most optimized to improve survival.